2013
DOI: 10.3233/jad-130050
|View full text |Cite
|
Sign up to set email alerts
|

Natural Cannabinoids Improve Dopamine Neurotransmission and Tau and Amyloid Pathology in a Mouse Model of Tauopathy

Abstract: Abstract. Cannabinoids are neuroprotective in models of neurodegenerative dementias. Their effects are mostly mediated through CB1 and CB2 receptor-dependent modulation of excitotoxicity, inflammation, oxidative stress, and other processes. We tested the effects of Sativex ® , a mixture of 9 -tetrahydrocannabinol and cannabidiol, acting on both CB1 and CB2 receptors, in parkin-null, human tau overexpressing (PK −/− /Tau VLW ) mice, a model of complex frontotemporal dementia, parkinsonism, and lower motor neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 58 publications
(88 reference statements)
2
74
0
Order By: Relevance
“…Activation of CB 2 receptor by the receptor agonists significantly decreased neuroinflammatory responses in the brains that received the injection of Ab (Fakhfouri et al 2012;Martin-Moreno et al 2011). Furthermore, similar anti-neuroinflammatory effects by cannabinoids were observed in APP transgenic and taupathy mice (Aso et al 2013;Casarejos et al 2013;MartinMoreno et al 2012). In addition to CB 2 receptors, CB 1 receptors appeared to downregulate neuroinflammation, as Aso et al showed that chronic treatment with the selective CB 1 receptor agonist, arachidonyl-2-chloroethylamide, reduced the astrocytic expression of the pro-inflammatory cytokine interferon-c in APP/PS1 transgenic mice (Aso et al 2012).…”
Section: Cannabinoidsmentioning
confidence: 65%
“…Activation of CB 2 receptor by the receptor agonists significantly decreased neuroinflammatory responses in the brains that received the injection of Ab (Fakhfouri et al 2012;Martin-Moreno et al 2011). Furthermore, similar anti-neuroinflammatory effects by cannabinoids were observed in APP transgenic and taupathy mice (Aso et al 2013;Casarejos et al 2013;MartinMoreno et al 2012). In addition to CB 2 receptors, CB 1 receptors appeared to downregulate neuroinflammation, as Aso et al showed that chronic treatment with the selective CB 1 receptor agonist, arachidonyl-2-chloroethylamide, reduced the astrocytic expression of the pro-inflammatory cytokine interferon-c in APP/PS1 transgenic mice (Aso et al 2012).…”
Section: Cannabinoidsmentioning
confidence: 65%
“…Finally, a Sativex-like combination of ⌬ 9 -THC:CBD is neuroprotective in the malonate-lesioned rat inflammatory model of HD (865) and improves dopamine neurotransmission and tau and amyloid pathology in a mouse model of tauopathies (123).…”
Section: Sativexmentioning
confidence: 99%
“…An interesting formulation to be investigated at the clinical level is the recently licensed phytocannabinoid-based medicine Sativex (GWPharma), which, based on the activity of its 2 components, Δ 9 -THC and CBD, at different complementary targets identified as neuroprotective in AD, e.g. CB 1 R and CB 2 R, PPARs, could become a promising novel disease-modifying therapy for patients with AD, as has been recently demonstrated in a preclinical model of an AD-related disorder (frontotemporal dementia) [103].…”
Section: Cannabinoids and Brain Damage In The Immature Brain: Neonatamentioning
confidence: 99%